Medical litigation experience of the victim of medical accident: a qualitative case study. Issue 1 (1st January 2019) - Pyo, Jeehee; Ock, Minsu; Han, Young-Joo
ABSTRACT: This study aims to demonstrate a comprehensive understanding of the life experience of victims of medical accidents after medical accidents and medical litigations. A single victim of a medical accident participated in the study. Six upper categories were derived as the results: "frustration and anger toward medical accident occurrence, " "desolated struggle for medical litigation, " "distrust of medical litigation related legal profession, " "accepting myself with a disability caused by a medical accident, " "a life with far more unexpected challenges as an athlete with disabilities, " and "find new meaning after the medical accident." The participant was experiencing physical and psychological distress in the process of accepting the medical accident and the disability. In addition, the participant was exposed to the secondary psychological distress from the medical profession, lawyer, and legal profession in the peculiar situation of medical litigation, and to the third psychological distress in life living as a disabled person.